Pengembangan Game Kuis Berbasis Android Menggunakan Kahoot Untuk Siswa Kelas V SDIT Darul Falah - Dedy Nurqori; Hawwin Fitra Raharja (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2023)
Technological advances in the form of smartphones are currently an example of how technical sophistication can be used to support learning activities. The use of gadgets, especially android operated by children, includes games. One alternative learning media that is considered capable of overcoming problems in the learning process is an android-based quiz game using kahoot, because this quiz game learning media students are able to play, learn, and be active in learning so that students' understanding in learning thematic material becomes better and memory students become more refined. The android-based quiz game using kahoot has a purpose, namely to determine the design of android-based quiz game development using kahoot, the quality of android-based quiz game products using kahoot, and the effectiveness of android-based quiz games using thematic subjects. This research procedure uses a 4D model, namely define, design, development, and dissemination. SDIT Darul Falah Jombang is the location chosen to carry out research on a large scale, with 18 students enrolled in the 2021/2022 academic year. Based on this research, it was found that the application of android-based quiz game media using Kahoot was included in the very good category with a total score of 89% according to three expert experts, including media experts with a percentage of 94% in the very good category, material experts with a percentage of 86% in the very good category, and RPP experts with a percentage of 88% in the very good category. While the effectiveness through the results of the student response questionnaire obtained a score of 88% including the very good category. Thus, it can be concluded that the android-based quiz game media using kahoot is feasible and effective in the learning process of the fifth grade students of SDIT Darul Falah Jombang.